Spin-polarized electronic reflections at metal-oxide interfaces - Da Costa, V; Iovan, A; Ounadjela, K; Allen, W; Gregg, J; Dieny, B (2002)
The ultra-thin oxide tunnel barrier employed in magnetic tunnel junctions stack has to be of very high quality in terms of large scale homogeneity of its thickness and height parameters. For controlling precisely oxidation kinetic, we used spin valves as an oxidation progress probe. By measuring the magnetoresistance effect versus the oxidation time we are able to detect under- or over-oxidation of the metallic material. This technique consists of analysing the ability of spin-dependent electron scattering at metal/oxide interfaces. (C) 2002 Elsevier Science B.V. All rights reserved.